Ceria–Vanadia/Silica‐Catalyzed Cascade for C−C and C−O Bond Activation: Green One‐Pot Synthesis of 2‐Amino‐3‐cyano‐4H‐pyrans - Maddila, Surya Narayana (ChemistryOpen, 2015)
We designed a ceria–vanadia/silica (Ce–V/SiO(2)) heterogeneous catalyst and used it for the green and efficient synthesis of 2‐amino‐3‐cyano‐4H‐pyran derivatives. The green reaction was a multicomponent one‐pot condensation of 5,5‐dimethylcyclohexane‐1,3‐dione, aromatic aldehyde, and malononitrile in an eco‐compatible solvent (ethanol). The catalyst was synthesized and fully characterized by powder X‐ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), and Brunauer–Emmett–Teller (BET) surface area analysis. The reported procedure offers a number of advantages including decreased reaction times, mild conditions, high yields, operational simplicity, and environmentally benign and simple work‐up procedures. Furthermore, the catalyst is economical, fully recyclable, and reusable for over five runs while preserving its high activity. The synthesized 2‐amino‐3‐cyano‐4H‐pyran products can later be used for pharmaceutical purposes.